The peoples of the Latin American Integration Route (RILA): tourist intersections - Leonel, Waldir (2023)
This article highlights the occupation of the first and countless peoples, such as the various indigenous ethnic groups, especially the Guarani peoples, British, Croatians, among others. Indeed, the achievements of these peoples allow viewing and understanding the local symbology that sets the tone and shape of the development of the Bioceânico project, which aims to reduce the arrival time of goods, facilitate exports and promote regional tourism. The scenario that runs through the Route was created by migrants who adjusted their stories to tourist mobility, which walks with the economic sector. This analysis dealt with spatiality, history, changes and permanence that occurred over time. The theoretical-methodological argments are present in the studies of authors who focus on subjects such as: material/imaterial cultural heritage, memory, space, place, territory/territoriality, reterritoriality and local  development. In this way, this academic area provides support for studies and research in the integration of peoples, tourist vocations and, consequently, locl development.